STRATEGI KEBIJAKAN INDUSTRI MARINE POLITAN UNTUK MENDUKUNG KONSEP MAMMINASATA: MODEL KONSEPTUAL DENGAN PENDEKATAN SISTEM DINAMIK - Mudiastuti, Retnani Dian; Nur, Taufiq; Sudirman, Sudirman (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2014)
Abstract South Sulawesi is a central Sulawesi Economic corridor flagship program in fisheries and marine sector. It has not been able to contribute significantly. On the other hand, is currently developing the construction of South Sulawesi instead focused on the development of the urban sector only through the concept Mamminasata (Makassar, Maros, Sungguminasa and Takalar),Â whereas the potential wealth of marine fisheries and South Sulawesi was very abundant . A development model that is able to integrate urban development and coastal development strategy oriented industrial and marine fisheries in the context of the region to support the Marine Politan Mamminasata as centrum and marine fisheries in Sulawesi. The purpose of this research is to develop a conceptual model related to the concept of holistic development of fisheries and marine industries as well as its relationship to the development of the city, so it can recommend appropriate and effective policies are sustainable. The model is built using system dynamics approach to generate sub system. Subsystem subsystem that is built is the means of production, subsistence fisheries, fish processing subsystem , the subsystem of marketing, supporting infrastructure subsystem, the subsystem income (fishing communities and government), fisheries policy subsystems and subsystem Mamminasata policy.